PELATIHAN FOTOGRAFI DAN CITRA DIGITAL UNTUK MENINGKATKAN KUALITAS KONTEN DIGITAL AKUN BISNIS UMKM RUSUNAWA WONOREJO, SURABAYA - Ilham, Romi; Lindiawati, Lindiawati; Wulandari, Dewi Ayu; Delonix, Yudha; Renzina, Renzina; Supriyanto, Heri (Jurnal KeDayMas: Kemitraan dan Pemberdayaan Masyarakat, 2023)
The problem challenged by MSMEs in â€˜Rusunawaâ€™ ( a rented simple flat belonging to the local government of Surabaya), at Wonorejo, Rungkut District, Surabaya is the low market response due to the lack of the quality of photos of MSME products as digital content. Therefore the solution offered is learning and practicing photography and digital image. The output of the activity is photos and edited photos and digital product catalogs uploaded on social media (Instagram, WhatsApp Status, and WhatsApp Business). After the training, participants are Â able to create product photos for digital content. product photos made by the support Â of a mini studio, properties that support the technique of taking the right angle and lighting. In addition, participants were also able to edit photos with the applications of Â Photorrom and Canva. Assistance of the Team is provided by monitoring the quality of photos taken and shared on WAG. After the photo is considered good, then it will be uploaded as content on Instagram or on WA Business.